2017
DOI: 10.1088/1361-6382/aa9d32
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic numerical cosmology with silent universes

Abstract: Relativistic numerical cosmology is most often based either on the exact solutions of the Einstein equations, or perturbation theory, or weak-field limit, or the BSSN formalism. The Silent Universe provides an alternative approach to investigate relativistic evolution of cosmological systems. The silent universe is based on the solution of the Einstein equations in 1+3 comoving coordinates with additional constraints imposed. These constraints include: the gravitational field is sourced by dust and cosmologica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 98 publications
3
44
0
Order By: Relevance
“…Conjecture 2 (the cosmological gravitational entropy conjecture) together with Proposition 1 seem to be in contradiction with Conjecture 1 (the cosmological no-hair conjecture), which postulates that a universe with a positive cosmological constant will end up as a homogeneous and isotropic de Sitter model. In this Section we will test these conjectures using the Simsilun simulation [35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conjecture 2 (the cosmological gravitational entropy conjecture) together with Proposition 1 seem to be in contradiction with Conjecture 1 (the cosmological no-hair conjecture), which postulates that a universe with a positive cosmological constant will end up as a homogeneous and isotropic de Sitter model. In this Section we will test these conjectures using the Simsilun simulation [35].…”
Section: Resultsmentioning
confidence: 99%
“…The Simsilun simulation is based on the code simsilun 1 . The description of the code, equations, and its applications are described in the 'Methods Paper' [35]. The Methods Paper describes how one can use the Millennium simulation [36,37,38] to set up the initial conditions for the code simsilun.…”
Section: The Simsilun Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve distance estimates from measured redshifts, approaches have been developed to refine the assumption of a spatially homogeneous matter density distribution, among others, see Dyer & Roeder (1972), Dyer & Roeder (1973), Bonvin et al (2006), Bolejko et al (2011), or Bolejko (2018. Most importantly, for the degeneracies arising in the gravitational lensing formalism, Bolejko (2011) showed that the distance-redshift relation as defined by Equation (6) holds for spatially homogeneous universes and is a good approximation with negligible corrections for universes in which density perturbations along a line of sight average out.…”
Section: Distances and H0 In The Cosmic Backgroundmentioning
confidence: 99%
“…A comparison of such backreaction effects with observations has been undertaken in [9]. Furthermore numerical solutions of Einstein's equations for a Silent Universe show "that the spatial curvature emerges due to nonlinear evolution of cosmic structures" [10].…”
Section: Introductionmentioning
confidence: 99%